2017
DOI: 10.2151/sola.2017-040
|View full text |Cite
|
Sign up to set email alerts
|

Projection of Future Climate Change over Japan in Ensemble Simulations Using a Convection-Permitting Regional Climate Model with Urban Canopy

Abstract: This study investigates future changes in temperature and precipitation extremes over Japan by the end of the 21st century using ensemble simulations under the Representative Concentration Pathway 8.5 scenario projected by a convection-permitting regional climate model with a grid spacing of 2 km.For all ensemble members, the projected future climate indicates robust increases in the 99th percentile of hourly temperature over all regions of Japan. In contrast, the 99th percentile of hourly precipitation increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…Murata et al . () included four members simulating future climate over Japan, but only perturbed sea surface temperatures and not wider uncertainties were used in the driving conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Murata et al . () included four members simulating future climate over Japan, but only perturbed sea surface temperatures and not wider uncertainties were used in the driving conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, dynamical downscaling can be used to simulate such complex topographical effects. Previous studies have demonstrated that dynamical downscaling using a high-resolution nonhydrostatic regional climate model (RCM) can realistically reproduce total precipitation and extreme precipitation over Japan (Kanada et al 2010;Sasaki et al 2011;Nakano et al 2012;Murata et al 2015Murata et al , 2017. Thus, RCM simulations offer a promising approach to the more accurate evaluation of changes in TC precipitation as the climate continues to warm.…”
Section: Introductionmentioning
confidence: 99%
“…Such regional climate data are hopefully defined on the same grid as that of the National Land Numerical Information of a typically 1 km mesh issued by the Ministry of Land, Infrastructure, Transport and Tourism, Japan. Similar products as d4PDF are available for the Japanese domain of 5 km and 2 km meshes (Murata et al 2017), although the ensemble sizes are restricted to approximately four due to limited computer resources. Validating high-resolution outputs is not easy even when observations of AMeDAS are used, which is a high-density station data network at a spatial interval of approximately 20 km over Japanese Islands maintained by the JMA.…”
Section: Discussionmentioning
confidence: 99%
“…In SI-CAT, several dynamical downscaling studies for spatially refined risk assessments were performed with NHRCM of 5 km resolution. The 5 km model resolves hourly changes of precipitation with complex topography (Murata et al 2017). Uemura et al (2018) demonstrated the impact of the downscaling on river discharge in Hokkaido.…”
Section: Assessment Of Risks Due To Heavy Precipitation and River Flomentioning
confidence: 99%